2021 International Conference on Computing, Communication, and Intelligent Systems (ICCCIS) 2021
DOI: 10.1109/icccis51004.2021.9397196
|View full text |Cite
|
Sign up to set email alerts
|

Deep Neural Architecture for Face mask Detection on Simulated Masked Face Dataset against Covid-19 Pandemic

Abstract: The dangerous COVID-19 (SARS-CoV-2) is rising steadily and globally, with more than 72,851,747 confirmed cases observed to WHO including 1,643,339 deaths till 17 December 2020. The country's economy is now almost fully halted, people are stuck up and investment becomes deteriorating. So, this is turning to worry of the government for a development and health. Health organizations are often desperate for evolving decision-making innovations to overcome this viral virus and encourage people to receive rapid and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(15 citation statements)
references
References 11 publications
0
14
0
1
Order By: Relevance
“…Due to the sudden outbreak of the coronavirus epidemic, there is yet no comprehensive real-world masked face recognition benchmark. Evaluations on simulated masked images [59], [61] may result in questioned conclusions, and small-scale masked sets [10], [12], [17] can not comprehensively reflect the performance of algorithms. Real-world masked test set RMFRD [95] consists of 525 identities and 5K masked faces, but there exist annotation noises.…”
Section: Face Recognition Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the sudden outbreak of the coronavirus epidemic, there is yet no comprehensive real-world masked face recognition benchmark. Evaluations on simulated masked images [59], [61] may result in questioned conclusions, and small-scale masked sets [10], [12], [17] can not comprehensively reflect the performance of algorithms. Real-world masked test set RMFRD [95] consists of 525 identities and 5K masked faces, but there exist annotation noises.…”
Section: Face Recognition Evaluationmentioning
confidence: 99%
“…In contrast with simulated [59], [61] or relatively small [10], [12], [17], [95] masked test sets, a real-world comprehensive benchmark for evaluating MFR is developed in this work. Based on the SFR identities, we further collect masked faces for these celebrities.…”
Section: Test Set With Real-world Maskmentioning
confidence: 99%
“…In [35], the authors propose an advanced deep learning model for face mask detection in real-time video streams. In this regard, Negi et al [36] employ two well-known deep neural network architectures with transfer learning for face mask detection using the Simulated Masked Face Recognition Dataset. Recently, the focus has shifted to subject recognition in the presence of masks, which is nowadays known as Masked Face Recognition (MFR).…”
Section: Related Workmentioning
confidence: 99%
“…It can take images and pull out features layer after layer. New studies have shown that intelligent computer processor vision is getting better at things like finding brain and breast cancer [15], finding cars without helmets [16], and finding face masks [17]. During the review of extant literature, different deep neural networks [18]-[21] are used to find the correct results.…”
Section: Introductionmentioning
confidence: 99%